1981
DOI: 10.1007/bf02468953
|View full text |Cite
|
Sign up to set email alerts
|

Extented esophago-gastretomy as surgical treatment for carcinoma of the cardia

Abstract: With the object of designing a feasible and more radical surgical intervention for the treatment of carcinoma of the gastric cardia and improving the long term survival of these patients, a procedure was described which entails total esophagogastrectomy and resection of the distal pancreas, spleen and regional lymphnodes. The esophagus was mobilized via the diaphragmatic hiatus without thoracotomy. Intestinal continuity, installed isoperistaltically was restituted in the same operation using a segment of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Moreno-Gonzalez et al 16 in Spain, reported three cases of total esophagogastrectomy in advanced tumors of esophagogastric junction. Abularach C et al 18 in Chile, reported the same surgery in five cases of tumors of esophagogastric junction, patients with a mean age of 50 years, mean hospital stay of 20 days, without mortality.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreno-Gonzalez et al 16 in Spain, reported three cases of total esophagogastrectomy in advanced tumors of esophagogastric junction. Abularach C et al 18 in Chile, reported the same surgery in five cases of tumors of esophagogastric junction, patients with a mean age of 50 years, mean hospital stay of 20 days, without mortality.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The mainly indication for such a complex operation are restricted and tumors of esophagogastric junction, and the minority that affect large portions of the esophagus and stomach, extrapolating Siewert classification (14). The advanced nature of these tumors at the time of diagnosis, justifies the prognosis of patients 10,[14][15][16][17] . This characteristic is clear in this series of cases, of which 80% belonging to stages III and IV.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%